The Fatality Assessment and Control Evaluation program's role in the prevention of occupational fatalities. (1st September 2001) - Higgins, D N; Casini, V J; Bost, P; Johnson, W; Rautiainen, R
Abstract : Objectives —The objective of the Fatality Assessment and Control Evaluation (FACE) program is to prevent traumatic occupational fatalities in the United States by identifying and investigating work situations at high risk for injury and formulating and disseminating prevention strategies to those who can intervene in the workplace. Setting —The FACE program is a research program located in the Division of Safety Research, a division of the National Institute for Occupational Safety and Health (NIOSH). NIOSH is an agency of the United States government and is part of the Centers for Disease Control and Prevention. NIOSH is responsible for conducting research and making recommendations for prevention of work related illnesses and injuries. FACE investigators conduct traumatic occupational fatality investigations throughout the United States and provide technical assistance to 15 state health or labor departments who have cooperative agreements with NIOSH to conduct traumatic fatality surveillance, targeted investigations, and prevention activities at the state level. Methods —Investigations are conducted at the worksite using the FACE model, an approach derived from the research conducted by William Haddon Jr. This approach reflects the public health perspective that the etiology of injuries is multifactorial and largely preventable. FACE investigators gather information on multiple factors that may have contributed to traumatic occupational fatalities. Information on factors associated with the agent (energy exchange, for example, thermal energy, mechanical energy, electrical energy, chemical energy), host (worker who died), and the environment (the physical and social aspects of the workplace), during the pre-event, event, and post-event time phases of the fatal incident are collected and analyzed. Organizational, behavioral, and environmental factors contributing to the death are detailed and prevention recommendations formulated and disseminated to help prevent future incidents of a similar nature. Results —Between 1982 and the present, more than 1500 fatality investigations have been conducted and reports with prevention recommendations distributed. Findings have been published in scientific and trade journals; safety professionals and policy makers have used FACE findings for prevention efforts; and working partnerships have been formed to address newly emerging safety concerns. Conclusions —FACE investigations identify multiple factors contributing to fatal occupational injuries, which lead to the formulation and dissemination of diverse strategies for preventing deaths of a similar nature.